Structural redundancy as means of increase of cheading direction accuracy - Карачун, Владимир Владимирович; Мельник, Виктория Николаевна (Eastern-European Journal of Enterprise Technologies, 2012)
The analysis of errors of kursoukazaniya is conducted on the basis of three-sedate free gyroscope with twochannel autoindemnification of influence of external noises. The degree of influence of the dvukhkomponentnoy harmonic and polyhaploid tossing of fuselage is set on the drift of ax of figure in relation to the axes of podvesa. The effect of autoindemnification is analytically appraised in a twochannel chart